1999
DOI: 10.1108/eum0000000006914
|View full text |Cite
|
Sign up to set email alerts
|

The use of information and communication technologies in commercial libraries in the UK

Abstract: A survey undertaken between January and March 1998 investigated the use of information and communication technologies (ICT) in a sample of 120 industrial and commercial libraries. Ninety-six per cent of the organisations which responded to the questionnaire use computers for some aspect of their library and information services. ICT was used for a range of office and other applications including, in rank order, e-mail, word processing, spreadsheets, presentation packages and database management systems. Ninety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Furness and Graham (1996) reported that 95 per cent of the special libraries in the UK used computers for some aspects of library and information services and used a wealth of different software packages depending upon particular applications. Barlow and Graham (1999) found that the majority of the commercial libraries in UK used commercial online databases.…”
Section: Ict Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Furness and Graham (1996) reported that 95 per cent of the special libraries in the UK used computers for some aspects of library and information services and used a wealth of different software packages depending upon particular applications. Barlow and Graham (1999) found that the majority of the commercial libraries in UK used commercial online databases.…”
Section: Ict Infrastructurementioning
confidence: 99%
“…Furness and Graham (1996) found that the library catalogue was the most popular aspect of automation in special libraries in the UK. Barlow and Graham (1999) reported that the use of purchased software packages for typical library housekeeping operations, such as cataloguing and circulation was more prevalent than in‐house developed systems in commercial libraries in the UK. They also found that the library catalogue was the most popular area for automation.…”
Section: Library Automationmentioning
confidence: 99%